Molecular Genetic Testing in Endocrinology—A Practical Guide - Kirmani, Salman (Endocrine practice, 2012)
To discuss the factors to consider when evaluating patients with a suspected genetic endocrine disorder, so as to guide practicing endocrinologists through the process of genetic testing and result interpretation. The author's experience and review of appropriate literature have been used to give a personal perspective on the role of genetic testing in hereditary endocrine disorders. Recent advances in our understanding of genetics and genomics have uncovered that they have a far more important role in the pathogenesis of endocrine disease than previously appreciated. Not only are we expanding our understanding of rare mendelian disorders such as multiple endocrine neoplasia type 1 and 2, but we are also beginning to understand the clinical significance of genetic factors in the pathogenesis of common disorders such as obesity and dyslipidemia. It can be difficult to appreciate the clinical significance and utility of genetic testing that is currently available, and the interpretation of genetic test results can be challenging. Decisions on whether genetic testing is needed should be made on a case-by-case basis, with the endocrinologist and geneticist working together from the outset.